2019
DOI: 10.1542/peds.2018-1902
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine Effectiveness and Herd Protection in Young Women

Abstract: BACKGROUND: Clinical trials of the 4-valent human papillomavirus (HPV) vaccine demonstrate high efficacy, but surveillance studies are essential to examine the long-term impact of vaccine introduction on HPV prevalence in community settings. The aims of this study were to determine during the 11 years after vaccine introduction the prevalence of (1) vaccinetype HPV in adolescent and young adult women who were vaccinated (to assess vaccine effectiveness) and (2) vaccine-type HPV in women who were unvaccinated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 35 publications
0
40
0
2
Order By: Relevance
“…Falls are largest with higher coverage and multiple cohorts vaccinated [3]. Herd protection has been demonstrated in studies that have evaluated pre and post vaccination HPV prevalence in males with female only vaccination program [4], as well as in unvaccinated women [5]. Although HPV being an STI may pose an impediment to acceptance of HPV vaccination in some communities (cancer prevention messages are a more effective strategy to achieve high coverage), it does make HPV potentially easier to control in a population that traditional vaccine preventable diseases which are spread by airborne transmission (eg measles) or faecal oral routes (eg polio).…”
Section: Impact On Infectionmentioning
confidence: 99%
“…Falls are largest with higher coverage and multiple cohorts vaccinated [3]. Herd protection has been demonstrated in studies that have evaluated pre and post vaccination HPV prevalence in males with female only vaccination program [4], as well as in unvaccinated women [5]. Although HPV being an STI may pose an impediment to acceptance of HPV vaccination in some communities (cancer prevention messages are a more effective strategy to achieve high coverage), it does make HPV potentially easier to control in a population that traditional vaccine preventable diseases which are spread by airborne transmission (eg measles) or faecal oral routes (eg polio).…”
Section: Impact On Infectionmentioning
confidence: 99%
“…6 Studies have demonstrated that HPV vaccines not only have high efficacy in clinical trials, but also high effectiveness in realworld settings: we have demonstrated that 4-valent vaccine-type HPV detection decreased from 35%-6.7% (80.9% decline) among vaccinated women, demonstrating vaccine effectiveness, and decreased from 32.4%-19.4% (40% decline) among unvaccinated women, demonstrating herd protection. 7 Vaccination may also result in cross-protection; that is, protection against HPV types genetically related to vaccine types, because HPV16 is genetically related to other A9 types and HPV18 is genetically related to other A7 types. It has been hypothesized that anti-HPV16 and anti-HPV18 antibodies generated by vaccination may bind to and neutralize HPV virions genetically related to HPV16 or HPV18, given the polyclonal immune response to vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…HPV vaccines are effective and have signi cantly reduced rates of genital warts, HPV infections, and cervical lesions among women (6). A recent surveillance study found evidence of HPV vaccine effectiveness and herd immunity among young women (7). The Advisory Committee on Immunization Practices (ACIP) recommends a two-dose HPV vaccination series for both boys and girls between 11 and 12 years of age; however, in the U.S., uptake of the HPV vaccine is slow.…”
Section: Introductionmentioning
confidence: 99%